2007
DOI: 10.1021/ac061972d
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric l-Lactate Sensor Based on Sol−Gel Processing of an Enzyme-Linked Silicon Alkoxide

Abstract: A novel organically modified silica material has been prepared by covalent linking of the carboxylic acid group of lactate dehydrogenase to the amino group of an organoalkoxysilane precursor via a carbodiimide coupling reaction during the sol-gel process. The material was used to fabricate a leak-free biosensor. The experimental variables and characteristics of the biosensors were studied by electrochemical methods. Results showed that the coenzyme concentration, mediator concentration, and electrode rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…The first one involved the use of polymeric additives (e.g., poly(vinyl alcohol), poly(vinyl pyridine), Nafion, poly(styrene sulfonate), chitosan) in the starting sol [28,29] or the resort to organosilane reagents (e.g., trimethoxysilyl-propyl methacrylate) likely to generate threedimensional uniform structures ready for enzyme immobilization [30]. An original recent approach is the covalent linking of the carboxylic acid group of lactate dehydrogenase to the amino group of an organoalkoxysilane precursor via a carbodiimide coupling reaction during the sol-gel deposition process [31]. The second one (promotion of charge transfer) mainly involved the use of additives such as carbon nanotubes [32,33] or titania nanoparticles [34].…”
Section: Introductionmentioning
confidence: 99%
“…The first one involved the use of polymeric additives (e.g., poly(vinyl alcohol), poly(vinyl pyridine), Nafion, poly(styrene sulfonate), chitosan) in the starting sol [28,29] or the resort to organosilane reagents (e.g., trimethoxysilyl-propyl methacrylate) likely to generate threedimensional uniform structures ready for enzyme immobilization [30]. An original recent approach is the covalent linking of the carboxylic acid group of lactate dehydrogenase to the amino group of an organoalkoxysilane precursor via a carbodiimide coupling reaction during the sol-gel deposition process [31]. The second one (promotion of charge transfer) mainly involved the use of additives such as carbon nanotubes [32,33] or titania nanoparticles [34].…”
Section: Introductionmentioning
confidence: 99%
“…Для ефективної роботи біосенсора важливим є збереження активності фермента тривалий час за умови його розташуванням в безпосередній близькості до поверхні електрода. Для іммобілізації ферментів часто використовують методи на основі ковалентного зшивання ферментів між собою, або з білковою основою, фізичне включення ферментів в провідні чи непровідні полімери або гідрогель, а також комбінацію цих методів.Також є повідомлення, що для підвищення стабільності ферменту використовували золоті наночастинки, які спільно з лактатоксидазою іммобілізували в тривимірному гелі [10]. Тіольні зв'язки забез-печили фіксацію ферменту на наночастинках золота, а збільшення площі поверхні призвело до збільшення кількості іммобілізованих молекул ферменту.…”
Section: вступunclassified
“…Lin et al reported a strategy to combat leaching by covalently linking lactate dehydrogenase to an organoalkoxysilane precursor via a carbodiimide coupling reaction prior to sol-gel processing to form the sensor membrane. 145 The resulting material was coated on a glassy carbon electrode to prepare a lactate biosensor with good long-term operational stability (~1 week).…”
Section: Enzyme Biosensorsmentioning
confidence: 99%